0232 Impact of Mental Health on 10-Year Trends in Habitual Sleep Duration. (27th May 2020) - Khader, W S; Tubbs, A; Fernandez, F; Jean-Louis, G; Seixas, A A; Williams, N J; Chakravorty, S; Killgore, W D; Wills, C C; Grandner, M A
Abstract: Introduction: Public health efforts aimed at reducing the decline in habitual sleep duration have not been successful. It is possible that this decline is differentially experienced relative to individuals' mental health status. This would further support the need to focus on mental health as a strategy for improving sleep in the general population. Methods: We examined 10 years of the National Health Interview Survey data (N=305, 555). During all years, habitual sleep duration, age, sex, race/ethnicity, and height and weight (used to compute body mass index) were recorded in the same way. In addition, depressed mood in the past 30 days was evaluated (coded as none, mild, moderate, or severe). Weighted regression analyses examined sleep duration as an outcome, year and depressed mood as predictors, and sociodemographics as covariates. A year-by-depressed mood interaction was computed, and analyses were stratified by group. Results: There was a significant year-by-depression interaction on linear change in sleep duration over the 10 year period (p=0.0001). Analyses were then stratified by depressed mood. In adjusted analyses, individuals with no depressed mood lost an average of 0.68 minutes of sleep per year (95%CI -0.82, -0.55; p<0.0001). Among those with mild depression, this was 7% higher, at 0.73 minutes (95%CI -1.13, -0.33; p<0.0001). Among those with moderate depressed mood, this was 154% higher, at 1.73 minutes lost per year (95%CI -2.31, -1.16; p<0.0001). Among those with severe depressed mood, this was 351% higher, at 3.07 minutes per year (95%CI -4.22, -1.92; p<0.0001). Conclusion: The 10-year linear decline in habitual sleep duration seems to depend on mental health status. Individuals with better mental health lose less sleep over time, relative to those with worse mental health. This highlights the importance of mental health as a possible avenue for improving sleep health in the population. Support: Dr. Grandner is supported by R01MD011600